The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1517-86922014200500714
|View full text |Cite
|
Sign up to set email alerts
|

Potência atada na máxima fase estável de lactato e índices do desempenho aeróbio de nado

Abstract: RESUMOIntrodução: A perspectiva do nado atado constituir um contexto válido para a avaliação aeróbia de nadadores foi investigada no presente estudo. Objetivo: Analisar a relação entre a potência em máxima fase estável de lactato no nado atado (P AtadaMFEL ) com seu respectivo índice em nado desimpedido (velocidade em MFEL, v MFEL ) e com outros índices da aptidão aeróbia e desempenho de nado crawl. Métodos: Dez nadadores (16,6 ± 1,4 anos) foram submetidos às estimativas de: (a) P AtadoCrítica (transformação d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Moreover, these conversions revealed that, except for rowing, all other exercise modalities exhibited similar m CP 2 MLSS % effects when expressed in terms of power output. Hence, from a practical standpoint, if a speed comparison is of interest, the effects of swimming, rowing, and kayaking should be divided by 3 (67,113).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these conversions revealed that, except for rowing, all other exercise modalities exhibited similar m CP 2 MLSS % effects when expressed in terms of power output. Hence, from a practical standpoint, if a speed comparison is of interest, the effects of swimming, rowing, and kayaking should be divided by 3 (67,113).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these conversions revealed that, except for rowing, all other exercise modalities exhibited similar μCPMLSS% effects when expressed in terms of power output. Hence, from a practical standpoint, if a speed comparison is of interest, the effects of swimming, rowing, and kayaking should be divided by 3 (67,113).
Practical Applications
This review study no longer provides a definitive solution to the heated debates in the literature regarding the most reliable threshold for heavy-severe exercise intensities.
…”
Section: Discussionmentioning
confidence: 99%
“…Swimming tethered by an inelastic wire attached to a resistance, which prevents swimmer displacement in water, has offered a realistic condition to simulate unimpeded swimming (i.e., free condition) [ 1 ], therefore enabling the measurements of force during stroke (arms) and kicking (legs) movements [ 2 , 3 , 4 , 5 ] as well as the assessment of the physiological responses while simulating incremental or constant exercise modes [ 6 , 7 , 8 , 9 ]. From the physiological assessments, the results have demonstrated similarities between tethered and unimpeded swimming conditions with regard to the responses of cardio-circulatory [ 10 ] and respiratory [ 6 , 11 , 12 ] systems, blood lactate concentration [ 7 ], and energetics contribution [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the context of constant exercise, there is a lack of information to support the physiological description of rest-to-work transition during tethered swimming, which might be useful to provide the necessary metabolic adjustment to reach muscular energy requirements, as has been observed by means of VO 2 kinetics (VO 2 k) in unimpeded swimming for the characterization of exercise domains [ 14 , 15 ], performance in distance races [ 16 , 17 , 18 ], exercise tolerance (i.e., time limit) in continuous [ 19 , 20 , 21 , 22 , 23 ] and intermittent trials [ 24 , 25 ], and comparisons to other exercises modes [ 26 ]. In fact, there are findings comparing constant exercise performance and blood-lactate response during tethered to unimpeded swimming conditions [ 7 ], but the VO 2 k was not analyzed and therefore not compared. Hence, unsupported by VO 2 k analysis, the inferences on the respiratory (i.e., gas diffusion), circulatory (i.e., blood perfusion), and metabolic (i.e., aerobic and anaerobic energy sources) responses during tethered swimming are insufficient to recognize whether the underlying physiological process determining muscle tolerance, or its limitations in relation to metabolic acidosis, is not different to the well-described mechanisms for unimpeded swimming.…”
Section: Introductionmentioning
confidence: 99%
“…Papoti et al21 e Pessoa-Filho, Greco e Denadai22 , é possível afirmar que o metabolismo predominante ainda seja o anaeróbio lático (glicogênio muscular), embora parte da energia seja fornecida pela glicólise aeróbia em razão da duração média da prova dos 400 m livre (275 segundos). Neste sentido, parece que os comportamentos de risco para os TA podem tanto atenuar os estoques de glicogênio muscular quanto dificultar a velocidade de fornecimento de energia pelas vias oxidativas, explicando assim, os achados para os 400 m livre.Os achados revelaram efeito significante da maturação biológica no desempenho nas provas da natação.…”
unclassified